2017
DOI: 10.1038/s41598-017-08095-7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation impairs Bach1 dependent HO-1 activation and increases sensitivity to oxidative stress in SH-SY5Y neuroblastoma cells

Abstract: Neuronal adaptation to oxidative stress is crucially important in order to prevent degenerative diseases. The role played by the Nrf2/HO-1 system in favoring cell survival of neuroblastoma (NB) cells exposed to hydrogen peroxide (H2O2) has been investigated using undifferentiated or all-trans retinoic acid (ATRA) differentiated SH-SY5Y cells. While undifferentiated cells were basically resistant to the oxidative stimulus, ATRA treatment progressively decreased cell viability in response to H2O2. HO-1 silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 60 publications
6
28
0
Order By: Relevance
“…Interestingly, while HO-1 protein levels were almost undetectable by means of a standard WB technique in untreated MeOV-1 and MeTA cells, HO-1 mRNA was detectable. Similar results have been obtained by our group in neuroblastoma cells 29,30 and by other authors in podocytes 31 and macrophages 32 highlighting the involvement of specific miRNA in the regulation of HO-1 protein expression. This aspect has not been evaluated in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, while HO-1 protein levels were almost undetectable by means of a standard WB technique in untreated MeOV-1 and MeTA cells, HO-1 mRNA was detectable. Similar results have been obtained by our group in neuroblastoma cells 29,30 and by other authors in podocytes 31 and macrophages 32 highlighting the involvement of specific miRNA in the regulation of HO-1 protein expression. This aspect has not been evaluated in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, PLX4032 specifically inhibits BRAF V600 significantly improving the patient survival rate. Similar results have been obtained by our group in neuroblastoma cells 29,30 and by other authors in podocytes 31 and macrophages 32 highlighting the involvement of specific miRNA in the regulation of HO-1 protein expression. 27 We took into consideration HO-1 as possible limiting factor of PLX4032 efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, we recently showed that HO-1 dependent endogenous generation of bilirubin is responsible for neuroblastoma cell resistance to H 2 O 2 but the efficiency of HO-1 induction decreases with neuronal differentiation, underlining the idea that neuronal commitment can reduce HO-1 dependent adaptability [64]. Other authors proved that CO inhibits the activation of AMP-activated protein kinase (AMPK) which is implicated in the β-amyloid induced toxicity [65].…”
Section: Ho-1 Protective Effects In Nervous Systemmentioning
confidence: 99%
“…Therefore, the effect of CBD-mediated HO inhibition will result in further increased stress, triggering HO-1 induction. HO inhibition or silencing has been shown to sensitize cells towards an additional (oxidative) stressor [85,86]; but at the same time inhibition of HO activity acts as a HO-1 inducing stimulus [84]. Such stress-triggered super-induction may increase stress tolerance in surviving cells via HO super-induction.…”
Section: Acceleration Of In Vitro Heme Converting Capacity By Treatmementioning
confidence: 99%